Politics, Ontology, Language. Giorgio Agamben and the Presupposing Apparatus - Oliva, Stefano (Rivista Italiana di Filosofia del Linguaggio, 1970)
Among the philosophers of the so-called Italian Theory, Giorgio Agamben has a special place thank to his deep influence and his original reflections about Politics, Ontology and Philosophy of Language. In this paper I propose a short reconstruction of Agamben’s thought in order to illuminate the “presupposing apparatus” that, according to the Italian philosopher, presides at the typical operation of human form of life in Western Tradition. The presupposing apparatus, discovered by Agamben in the analysis of Politics and Ontology, operates in the language following a mechanism of exception in which something is divided and rejected but, precisely through this exception, it is included as foundation of the opposite term. In this perspective the event of language, coinciding with the anthropogenesis, operates a triple exclusion: between linguistic and non-linguistic; between the animal who has language and animals which have not; between the essence of the linguistic animal and his existence – his bare life. At the end of Agamben’s itinerary, the mechanism of exclusion is assumed as the main political, ontological and linguistic structure that defines the human form of life. After clarifying Agamben’s account of language, I will present his concept of inoperativity as a solution for the impasse of Western tradition.